Skull defect – Frontotemporal dementia sagging brain syndrome - Wouter I. Schievink; Marcel M. Maya; Robin Babadjouni; Angelique Sao‐Mai S. Tay; Rachelle B. Taché (Annals of Clinical and Translational Neurology)
Abstract Objective Frontotemporal dementia (FTD) sagging brain syndrome is a disabling condition. An underlying spinal Cerebrospinal fluid leak can be identified in only a minority of patients and the success rate of non‐directed treatments is low. Some of these patients have a remote history of craniectomy/cranioplasty and we report a positive response to custom implant cranioplasty revision many years after their initial cranioplasty. Methods We reviewed medical records and imaging studies of 61 consecutive patients with FTD sagging brain syndrome. A SIH Disability Assessment Score (SIHDAS) questionnaire was completed to assess the severity of the symptoms before and after custom implant cranioplasty. Pre‐ and post‐operative brain MRI was obtained to assess degree of brain sagging. Results Eight (13.1%) of the 61 patients had a history of craniectomy/cranioplasty 1.5–13.5 years prior to onset of symptoms of FTD sagging brain syndrome. The mean age of the one woman and seven men at the time of presentation to our medical center was 50 years (range, 26–68 years). None had sinking scalp flap syndrome. Prior treatments included epidural blood patching and dural reduction surgery. Custom cranial implant surgery was performed in four patients and resulted in prompt and remarkable improvement of symptoms in three patients (SIHDAS: very severe disability to no or mild disability) and mild improvement in one patient. Brain MRI showed improvement of brain sagging. Interpretation A disproportionate number of patients with FTD sagging brain syndrome have a remote history of supratentorial craniectomy/cranioplasty and revision cranioplasty should be considered.